Understanding food principles and preparation - Brown, Amy (Wadsworth, 2008)
A guide to learning about foods, food preparation, food service, and food science. It helps you prepare for various careers in the food industry. It explores science of food through material on food selection and evaluation, food safety and food chemistry. It covers many aspects including meal planning, food preparation, and food preservation.